Thai Politics after the 2014 Coup and the Concept of Conquered Free States of Machiavelli - Payakpun, Natdanai (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2023)
This academic article aims to study the social and political governance methods of the National Council for Peace and Order (NCPO) after the 2014 Military Coup to compare the relationship between the political phenomena of the period and the concept of Conquered Free States with their Laws and orders. As it appears in chapter 5. "The Prince" of Italian political philosopher, Niccolo Machiavelli. The results showed that the political and social form of government of the National Council for Peace and Order, led by General Prayut Chan-o-cha as the head. This is consistent with the concept of the country’s governance model after the seizure of power by the new ruler. There is an idea as follow 1) The new ruler should destroy everything of the former ruler in line with the announcement of the termination of the Constitution of the Kingdom of Thailand B.E. 2550 by the National Council for Peace and Order. As a result, the country’s socio-political structure at both the national and local levels is disrupted; and 2) The new ruler must closely control the activities of the state in order to stabilize himself and deter opposition from his opponents. This is in line with the centralization of power by the National Council for Peace and Order (NCPO) governments and the declaration of a state of emergency in many areas to prevent future seizure of power from the civilian government. The author suggests guidelines for building political strength in various sectors as follows: 1) Containing democratic governance courses suitable for all ages and 2) Opening public spaces for expressing political opinions, and 3) Increasing Decentralization of governance to locality.